HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY FOR THE SIMULTANEOUS ESTIMATION OF CEFOPERAZONE AND SULBACTAM IN RAT PLASMA AND ITS IMPORTANCE IN THERAPEUTIC DRUG MONITORING - KORAKE, SWATI; PAWAR, ABHISHEK; SURYWANSHI, SUSHANK; BOTHIRAJA, C.; PAWAR, ATMARAM (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: To study the Therapeutic drug monitoring and pharmacokinetics of marketed antibiotics formulation by developing a sensitive and specific Bioanalytical Chromatographic method. Methods: In the present study, we developed a rapid, sensitive and selective chromatographic method for simultaneous estimation of Cefoperazone (CEF) And Sulbactam (SAL) in male Wistar rat plasma. A novel liquid phase extraction method has adopted the preparation of plasma sample preparation. The CEF and SAL were eluted on a peerless Basic C18 (25 cm; 4.6 mm x 5 µm) column maintained at controlled environmental conditions. The gradient mobile phase comprised of 10 mmol ammonium acetate and acetonitrile. A UV detector was set at 250 nm and retention times for CEF and SAL were approximately 5.6 and 14.2 min, respectively. The proposed HPLC method was validated according to the US FDA guidelines with respect to the linearity, accuracy, precision, detection and quantitation limits, robustness and specificity. Results: Calibration curves of CEF and SAL were linear across the concentration range of 600-1000 and 6-10 µg/ml, with correlation coefficients (r2)>0.9977 and (r2)>0.9987, respectively. The limits of detection for CEF and SAL were 70.48 and 0.35 µg/ml, respectively. Additionally, CEF and SAL were stable in plasma for at least 24 h when stored at room temperature and 2-8 °C. Conclusion: The developed chromatographic method was effectively utilized to measure the plasma CEF and SAL concentrations in a pharmacokinetics study after intravenous injection to the healthy male Wistar rats.